Proprioceptive Focal Stimulation (Equistasi®) May Improve the Quality of Gait in Middle-Moderate Parkinson's Disease Patients. Double-Blind, Double-Dummy, Randomized, Crossover, Italian Multicentric Study - Peppe, Antonella; Paravati, Stefano; Baldassarre, Maria Giulia; Bakdounes, Leila; Spolaor, Fabiola; Guiotto, Annamaria; Pavan, Davide; Sawacha, Zimi; Bottino, Sonia; Clerici, Daniela; Cau, Nicola; Mauro, Alessandro; et al. (Frontiers in Neurology, 2019)
Abstract Objective: The object of the study was to evaluate the efficacy of Proprioceptive Focal Stimulation on Gait in middle – advanced Parkinson (PD) patients by a crossover, randomized, double Blind double-dummy study using Equistasi®, a nano-technological device of the dimension of a plaster which generates High-Frequency Vibration (FV). Background: The efficacy of Gait Analysis (GA) on evaluating gait modification on Parkinson’s disease (PD) Patients is already well known. Therefore, GA was recorded in a group of PD patients using Equistasi ® device and its placebo. Methods: Forty PD patients at their best on therapy were enrolled in the study. Patients were randomly assigned to receive active or sham stimulation for 8 weeks and, following a wash-out period, switched to an additional 8-week period with the reverse intervention. GA was performed at baseline and at the end of both 8-week treatment periods Clinical state was monitored by MDUPDRS part III. Results: Active stimulation induced a significant improvement in Mean Velocity (Velocity), Stride Length (SL), Stance (STA) and Double Support (DST) percentage, both in left and right stride. The ANOVA analysis using H&Y stage as a factor, showed that DST and MDUPDRS III score improved significantly more in the more severely affected subjects. Conclusions: The findings obtained in this randomized controlled study show the efficacy of mechanical focal vibration, as stimulation of the proprioceptive system, in PD and encourage further investigation. The effect of the device on more severe patients may open a new possibility to identify the most appropriate candidate for the management of gait disturbances and postural instability with FV delivered with Equistasi.